Small Molecules from Medicinal Plant Iris tectorum as Histidine Kinase Inhibitor to Resensitize β-Lactam-Resistant Escherichia coli - Youqi Ji; Yinhuan Wang; Zhangkai Xu; Danlei Chen; Zhendi Yu; Qingyi Shao; Xin Hong; Zishu Liu; Dongqing Cheng (Molecules)
Background: Due to the widespread use of broad-spectrum antibiotics, the problem of antibiotic resistance has become an increasingly serious global threat. One of the key mechanisms of Escherichia coli resistance to beta-lactam antibiotics is the production of beta-lactamase enzymes, which poses a dilemma for clinicians in selecting antibiotics when faced with resistant bacterial infections. However, research on the reversal of bacterial resistance is limited. Methods: This study involved the preparation of Iris tectorum extract and detection of its effects on antibiotics sensitivity, extended-spectrum beta-lactamase (ESBL) gene expression, and histidine kinase phosphorylation levels in β-lactam antibiotic-resistant Escherichia coli. Additionally, analyses of the active ingredients of Iris tectorum extract were conducted with a liquid chromatography–mass spectrometer, and the binding sites were predicted by molecular docking. Results: Iris tectorum extract could restore the sensitivity of Escherichia coli to beta-lactam antibiotics and reduce the expression levels of ESBL genes and histidine phosphorylation levels. The active ingredients of Iris tectorum extract may be irigenin and tectorigenin, and these two small molecules could bind to histidine kinase to inhibit phosphorylation. Conclusions: Iris tectorum extract may serve as an antibiotic adjuvant, restoring the sensitivity of antibiotic-resistant bacteria by inhibiting histidine kinase phosphorylation, thereby alleviating the problem of Escherichia coli resistance to β-lactam antibiotics.